The effect of income and smallholder characteristics on cultivation, harvesting, and post-harvest management of natural rubber - . Nurliza (Global Journal of Environmental Science and Management)
BACKGROUND AND OBJECTIVES: Indonesia is the second largest natural rubber producer, which it gets primarily from smallholders. However, smallholders are less and less competitive because of unsustainable agricultural practices, while there is huge potential for sustainable natural rubber. This study aimed to measure the effect of income and smallholder characteristics on cultivation, harvesting, and post-harvest management.METHODS: Mixed methods with non-probability sampling were used for 100 natural rubber smallholders in Kapuas Hulu Regency, West Kalimantan, Indonesia, one of the regional centers of Indonesian natural rubber. Partial least square path modeling was used with SmartPLS software to estimate the complex cause-effect relationships of smallholder and farm factors for adopting sustainable agricultural practices.FINDINGS: The effect of the relationship between income and smallholder characteristics on cultivation and income on post-harvest management was not significant. Age and education affected some harvesting parameters, such as tapping knives, bamboo and clean latex collection, and latex stimulus risk, and some post-harvest parameters, such as a risk of acid coagulation and storage. The worker's income source, based on off-farm, on-farm, or non-farm activities, affected harvesting parameters, including tapping knives, bamboo and clean latex collection, and latex stimulus risk.  CONCLUSION: This study offers empirical evidence for sustainable agriculture management. The acceptance of sustainable cultivation and management of rubber practices uses smallholder and farm factors as constraints since they do not form a homogenous group, and the theory of planned behavior failed to provide an effective way to explain the behaviors. Good agricultural practices must be used at all steps, including cultivation, harvesting, and post-harvest management, to prevent problems.